Modelagem matemática: um exemplo no ensino da engenharia mecânica - Medeiros Filho, Ricardo Hugo Nunes (2019)
Mathematics is seen as a subject that is rejected by most students; this fact is due to the lack of usefulness for the tools seen in the classroom. In order to explain a real case for some mathematical tools we will use a mechanical engineering problem that deals with the analysis of a unmanned aerial vehicle (UAV) of the type quadrotor, which uses tools such as matrices, linear map, derivative and integral. These vehicles have gained a lot of notoriety in recent years due to their simple handling. Thus, this paper aims to present the use of these mathematical tools to study the equations that guide the motion of these aircraft. For this, we presented a brief history about the UAVs, also presenting the importance of the ludic in the teaching of mathematics as a facilitator in learning, then presented the theory behind the problem, highlighting all the mathematical tools involved, and finally the equations that guide the control of a quadrotor. Thus it was possible to present the problem in a more comprehensive and detailed way. Thus, a real application for such tools was presented thus demonstrating the importance of the study of mathematics